Jane Eyre. - Brontë, Charlotte (Fincer Print Classic, 2023)
About the Book: Jane Eyre "Do you think, because I am poor, obscure, plain and little, I am soulless and heartless? You think wrong!"From a tragic childhood when she is abused physically and emotionally by her inhuman Aunt Reed to a youth when she falls in love with Edward Rochester-her Byronic employer at Thornfield where she works as a governess-only to learn on their wedding day about his lunatic wife, the passionate and principled Jane Eyre endures many a hardships and oppressions. And after she leaves Thornfield, reduced to destitution, the Rivers family becomes her benefactor. What happens when St. John Rivers, her cold clergyman-cousin, proposes to her?Will